Match profiles for establishing position specific rehabilitation for rugby union players - Villarejo, D.; Palao, J. M.; Toro, E. O. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study was to quantify and describe the frequency and type of actions in terms of playing positions. We collected data from 48 matches at the 2007 Rugby World Cup. We found statistically significant differences between forwards and backs in many of the studied variables. The back row playing position obtained higher average total runs in the following variables: attempted tackles, made tackles, ruck and maul, and run tight. The results can be used as reference values for designing rehabilitation protocols in the stages of recovery for each position, in terms of type of exercise, volume and intensity.